2016
DOI: 10.1038/bcj.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic vein thrombosis in myeloproliferative neoplasms: risk factors for recurrences in a cohort of 181 patients

Abstract: We retrospectively studied 181 patients with polycythaemia vera (n=67), essential thrombocythaemia (n=67) or primary myelofibrosis (n=47), who presented a first episode of splanchnic vein thrombosis (SVT). Budd–Chiari syndrome (BCS) and portal vein thrombosis were diagnosed in 31 (17.1%) and 109 (60.3%) patients, respectively; isolated thrombosis of the mesenteric or splenic veins was detected in 18 and 23 cases, respectively. After this index event, the patients were followed for 735 patient years (pt-years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 39 publications
7
105
0
1
Order By: Relevance
“…Clinical features and outcome of MPN patients with SVT (MPN‐SVT) have been reported in a number of studies, either monocentric series of consecutive cases or larger cooperative cohorts, with overall consistent findings regarding demographics and phenotype. In fact, SVT are known to occur more commonly in younger MPN patients, especially women; PV is the most frequent diagnosis; concomitant thrombophilia is reported in nearly a third of cases.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Clinical features and outcome of MPN patients with SVT (MPN‐SVT) have been reported in a number of studies, either monocentric series of consecutive cases or larger cooperative cohorts, with overall consistent findings regarding demographics and phenotype. In fact, SVT are known to occur more commonly in younger MPN patients, especially women; PV is the most frequent diagnosis; concomitant thrombophilia is reported in nearly a third of cases.…”
Section: Introductionmentioning
confidence: 73%
“…However, recognition of an underlying MPN can be challenging since portal hypertension, iron deficiency and/or hepatic ischemia may influence hematological parameters or inappropriately increase endogenous erythropoietin . JAK2 V617F mutation is a reliable marker of underlying MPN, being found in the vast majority (76%‐93%) of SVT in patients with overt MPN, as well as in 25%‐43% of unselected SVT . As such, JAK2 V617F screening is recommended for any SVT patient, to identify those MPN (15%‐17%) that would otherwise be missed .…”
Section: Introductionmentioning
confidence: 99%
“…Cytoreduction was used in 40–70% patients across registries and did not uniformly influence recurrence risk. However, abnormally high blood counts due to inadequate cytoreduction were present in over half the patients with recurrent thrombosis (De Stefano et al , 2016b) indicating the need for rigorous clinical monitoring of patients on cytoreduction. Venesection alone is not appropriate to treat PV and cytoreduction should be undertaken in the presence of SVT.…”
Section: Management Of Specific Situations In Polycythaemia Veramentioning
confidence: 99%
“…On this basis, PVrelated SVT is an indication for long-term anticoagulation. Several prospective and retrospective registry studies conclude that long-term anticoagulation reduces recurrence risk at splanchnic and other sites with an acceptable level of bleeding complications (Amitrano et al, 2007;Ageno et al, 2015;De Stefano et al, 2016b). Recurrence in the arterial circulation has been observed in patients not on anti-platelet agents (Hoekstra et al, 2011;De Stefano et al, 2016b).…”
Section: Splanchnic Vein Thrombosismentioning
confidence: 99%
“…Our study shows that history of previous venous thromboembolism and atrial fibrillation are the only independent risk factors for the increased risk of venous thromboembolism in patients with myelofibrosis. In this regard, the role of previous venous thrombosis as risk factor for future venous thromboembolism after diagnosis of MF has been described already, but the role atrial fibrillation in this specific group of patients hasn't yet been evaluated. However, atrial fibrillation was found to be associated with increased risk of venous thromboembolism in the general population .…”
Section: Discussionmentioning
confidence: 99%